Microscopic evaluation, ethnobotanical and phytochemical profiling of a traditional drug Viola odorata L. from Pakistan - Dastagir, Ghulam; Samra Bibi; Noor Ul Uza; Rainer W. Bussmann; Imran Ahmad; Samiullah (Ethnobotany Research and Applications, 2023)
Background: The present study encompassed a highly traded medicinal plant Viola odorata L. (Violaceae) for detailed Light and Scanning Electron Microscopy, ethnobotany and phytochemical evaluation. Phytochemical evaluation included ascorbic acid, nutritional, and phytochemical profile, and essential and fixed oil study. Even though each feature has its own limited taxonomic value but collectively these characteristics may be systematically important especially for the discrimination and identification of complex and problematic taxa. Methods: The aim was to study microscopy, histology and phytochemical composition of Viola odorata on the basis of ethnobotanical information cited in the literature. Methods: The microscopy, and phytochemical composition of V. odorata was studied using standard methods. Results: Anatomy of the plant parts depicted dicot histology. Stomatal study under LM and SEM, revealed the presence of diacytic and anisocytic type of stomata. Stomata were numerous on the lower epidermis of the leaf. SEM of the powder drug showed the presence of trichomes, calcium-oxalate crystals, pitted vessels, fibers, trichomes, pollen grains, parenchyma cells, pith cells and root hair, but some unknown tissues were also seen. Ascorbic acid, nutritional, and phytochemical profile was investigated according to the standard methods. Different parts of the plant contained various chemical constituents such as alkaloids, mucilage, anthraquninone, saponins, tannins, fats and oil, protein and starch. Quantification of phytochemicals revealed mucilage and tannins to be the highest as compared to saponins and alkaloids. Leaves had 0.00143 % essential oil and 0.396 % fixed oil. Ascorbic acid, nutritional, and phytochemical profile, and oil study revealed vitamin C, proximate and phytochemical composition of V. odorata. Conclusion: Overall, this study can be helpful for plant taxonomists to further analyze the species for phytochemical isolation. This will improve the regulatory process and reduce the risk of a quality breach. Keywords: Ethnobotany, Histology, Morphology, Phytochemical evaluation, SEM, Viola odorata L.